Legal Protection for Briquette Trademark Holders in Indonesia (Study on Decision Number 70pdt.Sus-HKI/Merek/PN Niaga.Jkt.Pst) - Syafira, Nimasgari Dhaeyu Wildan; Mashdurohatun, Anis (UNISSULA Semarang, 2025)
Brands are part of intellectual property rights that have been used for hundreds of years and play an important role in the world of advertising and marketing in the business world. The formulation of the problem in this study is, 1) How is the legal protection for Briket trademark holders in Indonesia, 2) What is the basis for the judge's consideration in Decision Number 70/Pdt.Sus-HKI/Merek/2019/PN Niaga. Jkt. Pst related to legal protection for trademark holders in Indonesia, 3) How should the legal protection for trademark holders in Indonesia be. This research method uses a Normative Juridical approach. Legal research in a Normative Juridical manner examines the implementation of positive legal provisions (legislation) factually in every specific legal event that occurs in society in order to achieve predetermined goals. The results of this study indicate that: Legal protection for briquette brand holders is only given to parties who register their brands in good faith. Therefore, parties who apply for trademark registration based on bad faith will not be given legal protection. 2) The basis for the judge's consideration in Decision Number 70 / Pdt.Sus-HKI / Merek / 2019 / PN Niaga. Jkt. Pst is Law Number 20 of 2016 concerning Trademarks and Geographical Indications related to legal protection for trademark holders in Indonesia. Consumer legal protection against passing off related to public misleading in Indonesia, namely consumers can report business actors who carry out unfair business competition to the Business Competition Supervisory Commission. 3) Legal protection for Trademark holders in Indonesia in the future will be carried out by repressive efforts or active efforts to protect registered briquette brands can be carried out with a complaint offense by filing a lawsuit for damages and a lawsuit for cancellation of Trademark registration or criminal lawsuits through law enforcement officers. Repressive legal protection is carried out if there has been a violation of Trademark rights. Article 76 of the Law on Trademarks and Geographical Indications provides protection to registered trademark owners to file lawsuits against other parties who unlawfully use trademarks that are essentially or wholly similar.